Studies in expansive learning learning what is not yet there - Engeström, Yrjö 1948- (Cambridge University Press, 2016)
"Professor Engström's exciting approach sees expansive learning as the central mechanism of transformation in societal practices and institutions. For researchers and practitioners in education, this book provides a conceptual and practical toolkit for creating and analyzing expansive learning processes with the help of interventions in workplaces, schools and communities. Chapters 1-3 situate the theory of expansive learning in the field of learning science. Chapters 4-8 contain empirical studies of expansive learning in various organizational settings (such as banks, schools and hospitals). In Chapters 9-10, the author looks at new challenges and possibilities arising from rapidly spreading 'wildfire' activities (disaster relief, for example) and from the methodology of formative interventions aimed at triggering and supporting expansive learning. This book provides an integrative account of recent empirical studies and conceptual developments in the theory of expansive learning, and serves as a companion volume to Learning by Expanding"...